2015
DOI: 10.1111/iwj.12555
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV infection among burn patients: is there a relationship with patients' outcomes?

Abstract: The aim of the present study was to determine the prevalence of human immunodeficiency virus (HIV) infection among acute burn patients and its impacts on patient's outcomes in an Iranian burn care hospital. A cross-sectional study was conducted in a tertiary burn care hospital in Iran, retrospectively reviewing the data records of all patients admitted between February 2011 and February 2012. The HIV status of all the patients was assessed in relation to clinical outcomes and the patient's prognosis. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“… 21 , 23 The only exception here is in patients who have AIDS and severe burns where the reported mortality was 100%. 3 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 23 The only exception here is in patients who have AIDS and severe burns where the reported mortality was 100%. 3 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…21,23 The only exception here is in patients who have AIDS and severe burns where the reported mortality was 100%. 3,22 The current understanding with infection control specialists in our hospital is that the patients should restart their HIV medication at their local clinic when discharged. This is done to avoid patients having to change medications because clinics do not have the same medication as the provincial hospitals and this protocol hopes to ensure better compliance.…”
Section: Infections Contribute To Mortality In Severe Burnsmentioning
confidence: 99%
“…In Iran, the prevalence of HIV infection classifi ed as being concentrated epidemics due to low incidence in the general population (0.02%), and high prevalence among injecting drug users, 13.8%. 8,36 The comprehensive report on HIV in Pakistan revealed that the number of people living with HIV is estimated to be 130000, (0.1%). 37 Generally, HIV infection is rapidly diagnosed based on the presence or absence of HIV antibodies.…”
Section: Discussionmentioning
confidence: 99%